A Study on Cryptography - Shaffali Wadhawan; Shilpa (International Journal of Engineering and Management Research, 2023)
The goal of the paper is to present a general understanding of network security and cryptography. The study and application of methods to protect communication in the presence of hostile conduct. On the other hand, using both software and hardware technologies, network security refers to a collection of regulations and configurations and data. Data that is kept in our systems as well as network and data transfer through wireless networks are protected using cryptography and network security. Through the use of codes (encryption), techniques like fusing words with images, and other methods to hide information, cryptography is a network security tool used to safeguard company data and communication from cyber attacks. The study and application of methods to protect communication against malicious behaviour is known as cryptography. On the other hand, using both software and hardware technologies, network security refers to a collection of regulations and configurations intended to safeguard the accessibility, integrity, and confidentiality of computer networks and data. Data that is kept in our systems as well as network and data transfer through wireless networks are protected using cryptography and network security[4].